A study on selected morbidities among mining workers in Goa - S., Kalyani; Vernekar, Preksha P.; Cacodcar, Jagadish A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Given the complexity of the underground work system, the accidents at mining site and associated occupational diseases are dysfunctions that reduce the efficiency, productivity and profitability of workers. The present study provides a profile of selected morbidities among mining workers in Goa. Methods: Data was obtained from the records of a Occupational Health Service (OHS) centre in Ponda, Goa that conducted periodic health check ups of mining workers employed in 4 open cast iron ore mines from 4 Talukas, 2 each from North and South districts of Goa. Patient records of 199 workers representing different categories of work were obtained and analyzed. Data primarily focussed on visual acuity, audiometry findings, spirometry reports, ECG and basic laboratory blood investigations. Results: Upon analysis of data, it was observed that a high proportion of workers (43.21%) had defective vision. Assessment of audiometry reports revealed that 22.61% of workers had some form of hearing loss. As much as 19 (9.5%) workers were hypertensive, 26 (13.06%) were diabetic and 26 (13.06%) were dyslipidaemic. As high as 40 (20.1%) workers had ECG changes while 5 (2.51%) had pulmonary function impairment. Conclusions: Mining workers suffer from various health problems, notably, hearing loss, visual impairment, pulmonary function abnormalities and non-communicable diseases. This study emphasizes the importance of pre-employment and periodic medical check-ups in the mining industry for timely detection and appropriate treatment of these health conditions among the mining workers.